2018
DOI: 10.1080/17512433.2018.1478725
|View full text |Cite
|
Sign up to set email alerts
|

Gemtuzumab ozogamicin for the treatment of acute myeloid leukemia

Abstract: Gemtuzumab ozogamicin (GO) is an antibody-drug conjugate consisting of a monoclonal antibody targeting CD33 linked to a cytotoxic derivative of calicheamicin. Despite the known clinical efficacy in relapsed/refractory acute myeloid leukemia (AML), GO was withdrawn from the market in 2010 due to increased early deaths witnessed in newly diagnosed AML patients receiving GO + intensive chemotherapy. In 2017, new data on the clinical efficacy and safety of GO administered on a fractionated-dosing schedule led to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 44 publications
0
57
0
Order By: Relevance
“…However, in a report of 23 consecutive patients given GO for AML who relapsed following HSCT, liver injury consistent with VOD/SOS occurred in almost half (n = 11); histology studies suggested that GO toxicity resulted from its targeting of CD33 + cells in hepatic sinusoids [52]. In 2010, GO was withdrawn from the market owing to an association of GO plus intensive chemotherapy with increased early deaths in patients with AML, as well as phase III clinical trial evidence showing no evidence of overall survival benefits [56,57]; it was reapproved for AML in 2017 based on efficacy and safety data for GO administered with a fractionated dosing schedule [58,59].…”
Section: Antibody-drug Conjugates and Vod/sos Riskmentioning
confidence: 99%
“…However, in a report of 23 consecutive patients given GO for AML who relapsed following HSCT, liver injury consistent with VOD/SOS occurred in almost half (n = 11); histology studies suggested that GO toxicity resulted from its targeting of CD33 + cells in hepatic sinusoids [52]. In 2010, GO was withdrawn from the market owing to an association of GO plus intensive chemotherapy with increased early deaths in patients with AML, as well as phase III clinical trial evidence showing no evidence of overall survival benefits [56,57]; it was reapproved for AML in 2017 based on efficacy and safety data for GO administered with a fractionated dosing schedule [58,59].…”
Section: Antibody-drug Conjugates and Vod/sos Riskmentioning
confidence: 99%
“…Free calicheamicin exerts its effect into the nucleus, where it binds DNA and induces double strand breaks, leading to cell cycle arrest and apoptosis. In principle, stem cells and non-hematopoietic cells should not be affected by this agent due to lack of CD33 expression [164]. The clinical trial aims at evaluating if giving CPX-351 and gemtuzumab ozogamicin may work better in treating patients with AML, compared to giving only one of these therapies alone.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…withdrawn from the market in 2010, due to increased early deaths seen in newly diagnosed AML patients receiving this agent in combination with intensive chemotherapy. However, in 2017, new data based on a fractionated dosing schedule supported its re-approval for patients with newly diagnosed and R/R AML [12,14].…”
Section: Adcs Approved For the Treatment Of Hematologic Malignanciesmentioning
confidence: 99%
“…Factors that affect the mAb affinity for antigen and the ability to elicit immune effector functions (e.g. Gemtuzumab ozogamicin targets CD33, which is expressed on hematopoietic cells of the myeloid lineage and myeloblasts in >80% of patients with AML [12]. Brentuximab vedotin targets CD30, a member of the tumor necrosis factor receptor family, expressed on the Reed-Sternberg cells in Hodgkin lymphoma and ALCL cells.…”
Section: Article Highlightsmentioning
confidence: 99%